Maxillofacial prosthodontists are needed for the rehabilitation of patients with congenital and acquired craniofacial defects - Syed Murtaza Raza Kazmi; Khan, Farhan Raza (Journal of the Pakistan Medical Association, 2021)
Maxillofacial Prosthodontics (MFP) is a super-specialty of prosthodontics that involves around rehabilitation of patients presenting with congenital maxillofacial defects or craniofacial disabilities acquired due to disease such as cancer or trauma. (1) There are several types of prostheses that can be designed and fabricated by a maxillofacial prosthesis to improve the quality of life of patients. A simple classification is shown in figure 1. Continuous...